PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI PEMODERASI - Pratama, I Gede Gora Wira; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of capital structure and profitability of the company's value and managerial ownership in moderate capital structure and profitability of the company's value. This study uses data on property and real estate companies listed on the Indonesia Stock Exchange 2011-2013. The samples in this study using purposive sampling method, the number of observations by 36 sample. The data analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the regression analysis found that the moderation of capital structure and profitability affect the value of the company and managerial ownership able to moderate profitability is proxied by Return On Assets to the value of the company, while the managerial ownership is not able to moderate capital structure proxied by the Debt to Equity Ratio on firm value.
Keywords: debt to equity ratio, return on assets, managerial ownership, and the value of the company